АРАЛБОЙЫ РЕГИОНЫНДА ЭКОЛОГИЯЛЫҚ МАШҚАЛАЛАРДЫҢ ҚӘЎИПСИЗЛИГИН ТӘМИЙИНЛЕЎ МӘСЕЛЕЛЕРИ - Нурланов, А.С.; Джақсымуратов, К.М.; Гайпова, Р.Т. (FAN va JAMIYAT, 2019)
The consequence of drying the Aral Sea brought to the ecological crisis that in its turn brought to changing of the natural environment and made a negative influence on all branches of national economy in the Republic of Karakalpakstan. The author of the article studies the consequences of the ecological crisis in the natural environment, the main role and importance of rational use of natural resources.